ВИКОРИСТАННЯ РАДІОЧАСТОТНИХ ТРАНСФОРМАТОРІВ СТРУМУ ЗАМІСТЬ КОТУШОК РОГОВСЬКОГО У ВИСОКОВОЛЬТНОМУ ОБЕРТОВОМУ ОБЛАДНАННІ - Nurubeyli, T.K.; Nurubayli, Z.K.; Ismayilov, I.M.; Mammadova, G.N.; Muslumzade, A.R. (Інститут електродинаміки НАН України, Київ, 2025)
This paper presents a comparative study of the use of Radio Frequency Current Transformers (RFCT) and Rogowski Coils (RC) for partial discharge (PD) monitoring in high-voltage rotating equipment. The relevance of work lies in the need to enhance the accuracy and reliability of equipment diagnostics while maintaining its operational status during measurements. The authors focus on the technical aspects of both methods, analyzing sensitivity, accuracy and resistance to interference, ease of installation, and operational simplicity. The study demonstrates that RFCTs offer significant advantages, including from high sensitivity to low-amplitude signals, resilience to radio interference, and a wide frequency bandwidth. These features make RFCTs particularly effective for use in environments with intense external interference, such as radar signals at industrial sites. Moreover, RFCTs feature a design that simplifies installation and operation, reducing setup time and increasing cost-effectiveness. The analysis confirms the superior accuracy of RFCTs under real operating conditions, ensuring high-quality PD signal detection against noise, a capability difficult to achieve with RCs without additional filtering. The study highlights the potential of RFCTs for use in modern high-voltage equipment monitoring systems, offering a practical and economically efficient solution that improves power system reliability and helps prevent critical failures. References 16, figures 10, tables 2.